ANALYTICAL STUDY ON FULLY DEVELOPED MIXED CONVECTION COUETTE FLOW IN A VERTICAL CHANNEL WITH VISCOUS DISSIPATION EFFECT (FUDMA JOURNAL OF SCIENCES, 2024)
The study of mixed convection flow in a vertical channel with viscous dissipation has been examined. To solve the governing energy and momentum equations, the Homotopy perturbation method was employed. Graphs were generated to analyze the impact of the governing flow parameters. Numerical values for skin friction, rate of heat transfer, and mass flux were estimated. The study revealed that an increase in mixed convection expands the reverse flow region and raises the critical value of mixed convection that leads to flow reversal. Additionally, both fluid temperature and velocity rise with increased viscous dissipation, as higher viscous dissipative heat elevates temperature, subsequently increasing the buoyancy force.
Keywords: Couette flow; Mixed convection; Viscous dissipation; Homotopy perturbation method; Vertical channel